Caracterização molecular da microbiota e morfologia intestinal da tilápia-do-Nilo (Oreochromis niloticus) após suplementação dietética com mananoligossacarídeo (MOS) - Sotrati, Vanessa Vidoti [UNESP] (2014)
The intensification of tilapia production caused bacterial diseases frequent especially for high density storage and stressful handling. This scene brings unbridled and indiscriminate use of antimicrobials, producing a final product with dubious quality and damage to the environment. A promising alternative to prevent diseases in fish farming is the use of mannan oligosaccharide (MOS) in fish diet, which promotes the adsorption of pathogens in the intestine, improving the health of the animal. The aim of this study was to evaluate the use of mannan oligosaccharide in the characterization of the microbiota and intestinal morphology of Nile tilapia for 45 days of feeding. After seven days of mannan oligosaccharide supplementation, fish fed with diet containing 2 g kg-1 of the supplement had the lowest number of total aerobic bacteria (p<0.05) in the intestine when compared to the control group and the percentage of these bacteria was reduced the longer the feeding time (p <0.05). Fish fed all levels of mannan oligosaccharide supplementation showed a higher percentage of anaerobic bacteria and Bacillus sp. in the intestine (p<0.05) and the increasing number of these bacteria was observed in the group fed with 15 g kg-1 (anaerobic bacteria) and 8 g kg-1 (Bacillus) after 45 days. Histological analysis of tilapia intestine fed 10 g kg-1 mannan oligosaccharide for seven days showed microvilli width, height and total height superior to other levels of supplementation and the control group (p> 0.05), while the greater thickness of villi was observed in the fish diet with 8 g kg-1 mannan oligosaccharide in the same feeding period, however the villi width in period of 45 days in diet supplemented with 8 g Kg-1 mannan oligosaccharide it was significance in relation to control (p<0.05). The add of mannan oligosaccahride in diet of Oreochromis niloticus, from level of inclusion 2 g Kg-1 is able ...